Codification of the Law of International Treaties (to the 40th Anniversary of the Vienna Convention on International Treaties) - R. M. Valeev (Московский журнал международного права, 2009)
The article is devoted to the 40th anniversary of the Vienna Convention on International treaties. The author follows closely the milestones in the process of working out the Convention and shows how it effects the codification of the Law of International Treaties. He describes the work of the UN Commission of International Law over such topics as “Reservations to International Treaties”, “The effect of military conflicts on International Treaties”, “Treaties through the prism of times”.